Leading change for healthy communities and successful land reuse - United States Agency for Toxic Substances and Disease Registry.
"ATSDR's Brownfield/Land Reuse Health Initiative helps communities incorporate health considerations in land reuse decisions. People can turn vacant or underused land into places that benefit the whole community. ATSDR works with the U.S. Environmental Protection Agency (EPA), state and local officials, developers, and communities to include health in these types of projects. ATSDR promotes community health as part of redevelopment. There are many ways which we can assist the community. We may measure the level of chemicals in the body to determine if people are exposed to contaminants. We may communicate and educate communities on health risks in this community. We may evaluate health outcomes for certain diseases. We may assist in organizing the community to address identified health issues. The Leading Change for Health Communities and Successful Land Reuse is the 'how to' guide for all members of the development community to promote health as a part of redevelopment. The diverse community projects in this book represent some of the many examples of healthy redevelopment projects across the country." - foreword Introduction -- The Brass Site, Kenosha, Wisconsin -- Clearwater Brownfields Area, Clearwater, Florida -- Five Mile Creek, Jefferson County, Alabama -- Highland Park, Milwaukee, Wisconsin Keweenaw Bay Indian Community (KBIC), L'Anse Indian Reservation, Michigan -- Menomonee River Valley, Milwaukee, Wisconsin -- Moore Square Museums Magnet School, Raleigh, North Carolina -- Treasure Valley Institute for Children's Arts, Boise, Idaho -- Yukon River Inter-Tribal Watershed Council, Alaska and Yukon -- Resources "The findings and conclusions in this book are those of the authors and_do not necessarily represent the views of the Agency for Toxic Substances and Disease Registry." "The majority of the book is a series of case studies or 'success stories' showing redevelopment to achieve a variety of health-related goals: recreation/greenspace; quality, affordable housing; access to health care, community policing, and other services; education; revitalization of tribal lands; and new jobs and economic development to benefit the community . Each case study tells a story of how community health was successfully integrated into brown-fields redevelopment and land reuse, highlighting key elements such as leadership, financing and other resources tapped, stakeholder involvement, actions taken, measures of success, and lessons learned. We suggest that you browse through the book to glean ideas from each success story that are relevant to your community's situation." - p. 1 "Publication date: November 2010." Also available via the World Wide Web as an Acrobat .pdf file (7.45 MB, 96 p.).